Variability in Asthma Care and Services for Low-Income Populations among Practice Sites in Managed Medicaid Systems - Lozano, Paula (Blackwell Science Inc, 2003)
OBJECTIVE: To characterize and describe variability in processes of asthma care and services tailored for low–income populations in practice sites participating in Medicaid managed care (MMC). STUDY SETTING: Eighty-five practice sites affiliated with five not-for-profit organizations participating in managed Medicaid (three group-model health maintenance organizations [HMOs] and two Medicaid managed care organizations [MCOs]). STUDY DESIGN/DATA COLLECTION: We conducted a mail survey of managed care practice site informants using a conceptual model that included chronic illness care and services targeting low-income populations. The survey asked how frequently a number of processes related to asthma care occurred at the practice sites (on a scale from “never” to “always”). We report mean and standard deviations of item scores and rankings relative to other items. We used within-MCO intraclass correlations to assess how consistent responses were among practice sites in the same MCO. PRINCIPAL FINDINGS: Processes of care related to asthma varied greatly in how often practice sites reported doing them, with information systems and self-management support services ranking lowest. There was also significant variation in the availability of services targeting low-income populations, specifically relating to cultural diversity, communication, and enrollee empowerment. Very little of the site-to-site variation was attributable to the MCO. CONCLUSIONS: Our conceptual framework provides a means of assessing the provision of chronic illness care for vulnerable populations. There is room for improvement in provision of chronic asthma care for children in managed Medicaid, particularly in the areas of self-management support and information systems. The lack of consistency within MCOs on many processes of care suggests that care may be driven more at the practice site level than the MCO level, which has implications for quality improvement efforts.